Reversing the Colonial Gaze: Persian Travelers Abroad by Hamid Dabashi (American Journal of Islam and Society, 2020)
In his preface to Reversing the Colonial Gaze: Persian Travelers Abroad, Hamid Dabashi locates the origins of the book in the 2016 US presidential election, after which the newly-elected Donald Trump signed an Executive Order banning citizens of six Muslim-majority countries from entering the United States. The title itself explicitly demonstrates Dabashi’s determination to overturn the general attitude towards the travelogues under his scrutiny: Whereas “Europe was only part of their travels,” some categorize the Persian travelers for having focalized Europe as their sole destination (ix). While there is no denying that the travelers in question did indeed visit, and documented their observations of the continent, Europe was merely—and against the grain of Eurocentric scholarship—one leg of their journeys.Download